Hydrogen and chlorine abundances in the Kimberley formation of Gale crater measured by the DAN instrument on board the Mars Science Laboratory Curiosity rover. Issue 5 (14th May 2016) - Litvak, M. L.; Mitrofanov, I. G.; Hardgrove, C.; Stack, K. M.; Sanin, A. B.; Lisov, D.; Boynton, W. V.; Fedosov, F.; Golovin, D.; Harshman, K.; Jun, I.; Kozyrev, A. S.; et al.
Abstract: The Dynamic Albedo of Neutron (DAN) instrument on board the Mars Science Laboratory Curiosity rover acquired a series of measurements as part of an observational campaign of the Kimberley area in Gale crater. These observations were planned to assess the variability of bulk hydrogen and neutron‐absorbing elements, characterized as chlorine‐equivalent concentration, in the geologic members of the Kimberley formation and in surface materials exposed throughout the area. During the traverse of the Kimberley area, Curiosity drove primarily over the "Smooth Hummocky" unit, a unit composed primarily of sand and loose rocks, with occasional stops at bedrock of the Kimberley formation. During the Kimberley campaign, DAN detected ranges of water equivalent hydrogen (WEH) and chlorine‐equivalent concentrations of 1.5–2.5 wt % and 0.6–2 wt %, respectively. Results show that as the traverse progressed, DAN observed an overall decrease in both WEH and chlorine‐equivalent concentration measured over the sand and loose rocks of the Smooth Hummocky unit. DAN measurements of WEH and chlorine‐equivalent concentrations in the well‐exposed sedimentary bedrock of the Kimberley formation show fluctuations with stratigraphic position. The Kimberley campaign also provided an opportunity to compare measurements from DAN with those from the Sample Analysis at Mars (SAM) and the Alpha‐Particle X‐ray Spectrometer (APXS) instruments. DAN measurements obtained near the Windjana drill location show a WEH concentration of 1.5 wt %, consistent with the concentration of low‐temperature absorbed water measured by SAM for the Windjana drill sample. A comparison between DAN chlorine‐equivalent concentrations measured throughout the Kimberley area and APXS observations of corresponding local surface targets and drill fines shows general agreement between the two instruments. Key Points: Summary of DAN active measurements of the Smooth Hummocky unit in the Kimberley DAN demonstrates stratigraphic variation in the WEH and chlorine equivalent at different geological members of the Kimberley formation The analysis of DAN data has shown that WEH and Cl‐equivalent concentrations from DAN are consistent with APXS and SAM measurements